FROM THE PRACTICE OF APPLYING CRITERIA-BASED ASSESSMENT IN THE TEACHING OF COMPUTER SCIENCE AT SCHOOL - Хасенова, Айгерим; Карымсакова Анарa; Закирова , Алма (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article is devoted to criteria-based assessment, which is currently the only system for monitoring and testing students’ knowledge and skills. Also, the assessment of the new system of assessment is compared with the previous traditional system of assessment of knowledge in schools. Aims and objectives related to training, feedback and assessment have been written in the article. The purpose of criteria-based assessment is characterized as ensuring objectivity, reliability of information about students’ learning outcomes. Information on the development of a high level of students’ thinking has been provided. The article describes the stages of the transition of the Republic of Kazakhstan to the updated content of education, accompanied by the introduction of a new system of assessment. The updated content of knowledge includes research methods such as the analysis of formative and summative assessment, the role of criteria and descriptors in assessment. Observing and comparing, it can be said that the practical application of assessment criteria and assessment tools using Bloom’s taxonomy, mind map, modern applications, test developers help to develop cognitive reading, creative and critical thinking.